2015
DOI: 10.1186/s12885-015-1369-8
|View full text |Cite
|
Sign up to set email alerts
|

High expression of KPNA2 defines poor prognosis in patients with upper tract urothelial carcinoma treated with radical nephroureterectomy

Abstract: BackgroundTo analyze the expression of karyopherin alpha 2 (KPNA2) in upper tract urothelial carcinoma (UTUC) and to investigate whether the KPNA2 expression provides additional prognostic information following radical nephroureterectomy (RNU).MethodsA tissue microarray (TMA) containing samples from 176 patients with UTUC who underwent RNU at our institute was analyzed for KPNA2 expression using immunohistochemistry. KPNA2 expression in normal urothelial cell line and urothelial carcinoma cell lines was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…KPNA2 may play critical roles in carcinogenesis, cell differentiation, transcription regulation and immune response. Recently studies have demonstracted that high expression of KPNA2 is associated with poor prognosis of esophageal squamous cell carcinoma12, epithelial ovarian carcinamos13, gastric cancer14, prostate cancer15, upper tract urothelial carcinoma16 and breast cancer17. Teng et al .…”
Section: Discussionmentioning
confidence: 99%
“…KPNA2 may play critical roles in carcinogenesis, cell differentiation, transcription regulation and immune response. Recently studies have demonstracted that high expression of KPNA2 is associated with poor prognosis of esophageal squamous cell carcinoma12, epithelial ovarian carcinamos13, gastric cancer14, prostate cancer15, upper tract urothelial carcinoma16 and breast cancer17. Teng et al .…”
Section: Discussionmentioning
confidence: 99%
“…How KPNA2 contributes to tumorigenesis and the development of osteosarcoma is still unclear. Yoichi Miyamoto reported that functional importin α1 (KPNA2) is located at the cell surface and may accelerate the proliferation of cancer cells by affecting FGF1 signaling in cancer cells (24). Other studies also reported that microRNAs may regulate KPNA2 expression in cancers [25].…”
Section: Discussionmentioning
confidence: 99%
“…The value of nuclear transporters such as KPNB1, XPO1 and CSE1L as prognostic tools is still under investigation and data supporting this are only available for a select few cancers. In contrast, KPNA2 has been well established as a prognostic marker in various cancers including: breast cancer, brain cancer, gastric cancer, prostate cancer, ovarian cancer, bladder cancer, liver cancer, melanoma, lung cancer and oesophageal cancer . Dahl et al's research in breast cancer was the first to identify KPNA2 as a prognostic marker .…”
Section: Nuclear Transporters As Prognostic Markersmentioning
confidence: 99%